Melatonin reduces neuropathic pain behavior and glial activation through MT2 melatonin receptor modulation in a rat model of lysophosphatidylcholine-induced demyelination neuropathy. (November 2020) - Huang, Chun-Ta; Chen, Seu-Hwa; Chang, Chi-Fen; Lin, Shih-Chang; Lue, June-Horng; Tsai, Yi-Ju
Abstract: In this study, we investigated whether melatonin treatment prevents development of neuropathic pain via suppression of glial mitogen-activated protein kinases (MAPKs) activation in the cuneate nucleus (CN) in a lysophosphatidylcholine (LPC)-induced median nerve demyelination neuropathy model. Rats were fed orally with melatonin once a day at a dose of 37.5, 75, or 150 mg/kg 30 min before until 3 days after LPC treatment. Subsequently, behavioral tests were conducted on these animals, and immunohistochemistry and immunoblotting were used for qualitative and quantitative analysis of glia and MAPKs, including ERK, JNK, and p38, activation. Enzyme-linked immunosorbent assays were applied to measure pro-inflammatory cytokine responses. Furthermore, intra-CN microinjection of S26131 (MT1 receptor antagonist), 4P-PDOT (MT2 receptor antagonist), or prazosin (MT3 receptor antagonist) were performed to investigate the association between melatonin receptor subtypes and effects of melatonin on demyelination neuropathy. LPC treatment of the median nerve induced a significant increase in glial fibrillary acidic protein (GFAP; an astrocyte marker) and ED1 (an activated microglia marker) immunoreactivity in the ipsilateral CN and led to development of neuropathic pain behavior. Inspection of GFAP-immunoreactive astrocytes revealed that astrocytic hypertrophy, but not proliferation, contributed to increased GFAP immunoreactivity. Double immunofluorescence showed that both GFAP-immunoreactive astrocytes and ED1-immunoreactive microglia co-expressed p-ERK, p-JNK, and p-p38 immunoreactivity. Melatonin administration dose-dependently reduced neuropathic pain behavior, decreased glial and MAPKs activation, and diminished the release of pro-inflammatory cytokines in the ipsilateral CN after LPC treatment. Furthermore, 4P-PDOT, but not S26131 or prazosin, antagonized the therapeutic effects of melatonin. In conclusion, administration of melatonin, via its cognate MT2 receptor, inhibited activation of glial MAPKs, production of pro-inflammatory cytokines, and development of demyelination-induced neuropathic pain behavior. Highlights: Median nerve demyelination neuropathy contributed to microglial activation and astrocytic hypertrophy. Activated glia co-expressed phosphorylated MAPKs, including p-ERK, p-JNK, and p-p38. Melatonin prevented glial activation and MAPKs phosphorylation, and ameliorated demyelination-induced neuropathic pain. Melatonin via binding to its cognate MT2 receptor, to achieve therapeutic effects.